Preparation method of slump-retaining polycarboxylate superplasticizer

By using VPEG and methyl acrylate as the main monomers, combined with chitosan microsphere technology, the polycarboxylate water-reducing agent is prepared under normal temperature conditions, which solves the problems of complex processes and high costs in the existing technology, and realizes the polycarboxylate water-reducing agent Efficient synthesis and good performance of acid superplasticizer.

CN119350555APending Publication Date: 2025-01-24SHANDONG LUQIAO CONSTR MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411291544.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The synthesis process of existing polycarboxylic acid water reducing agents is complex and has high cost. Especially when preparing slump-retaining polycarboxylic acid water reducing agents, it is necessary to add slump-retaining functional monomers, which further increases the complexity and cost of the process.

Method used

Use VPEG as a large monomer, acrylic methyl ester as a collapse function, and synthesize through the synthesis of chitosan-acrylic composite microspheres and shell polycar-acrylic methyl ester, combined with ultrasonic dispersing and hot air flow spraying technology, realized in it in There is no need to add time -controlled polycarboxylic acid water reduction agent under normal temperature conditions.

Benefits of technology

A good synthesis of polycarboxylic acid reduction agents, simplifying the process, reducing costs, effectively controlling the aggregation process of acrylic acid and VPEG, avoiding the phenomenon of self -convergence and explosion, improving the decentralized performance of the product and the collapse of the product. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005044747740000021
    Figure BDA0005044747740000021
  • Figure BDA0005044747740000022
    Figure BDA0005044747740000022
  • Figure BDA0005044747740000051
    Figure BDA0005044747740000051
Patent Text Reader

Abstract

The invention discloses a preparation method of a slump-retaining polycarboxylate superplasticizer. Chitosan-acrylic acid composite microspheres synthesized by acrylic acid, hydroquinone and chitosan, and chitosan-methyl acrylate microspheres synthesized by chitosan, methyl acrylate and Rugaquinone and VC are poured into a mixed solution of VPEG, hydrogen peroxide and sodium hypophosphite to be stirred and react for 2 h, then cold water at the temperature of 0-10 DEG C is added, and after the temperature of the solution is 10 DEG C or below, the chitosan-acrylic acid composite microspheres and the chitosan-methyl acrylate microspheres are stirred and react for 2 h. And filtering and compressing to filter out a gel substance, thereby obtaining the slump-retaining polycarboxylate superplasticizer. The acrylic acid microspheres and the methyl acrylate microspheres are separately prepared, so that different polymerization retarding components can effectively realize targeted controlled polymerization for different monomers, a good polymerization process of polycarboxylic acid is realized, the polymerization temperature is controlled, and good performance of a product is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete admixtures, and in particular to a method for preparing a collapse-retaining polycarboxylate water-reducing agent. Background Art

[0002] Polycarboxylate water reducer is the most widely used and largest type of concrete water reducer. The synthesis of polycarboxylate water reducer often requires the free polymerization of different macromonomers initiated by initiators under specific temperature conditions. The synthesis temperature, synthesis time, and dosage of each component in the synthesis process will have a great influence on the water-reducing performance of polycarboxylate water reducer. In order to control the stability of the quality of polycarboxylate water reducer formed by free polymerization, it is often necessary to control the synthesis temperature range and control the free polymerization time and process by dripping AB materials separately, so as to avoid excessive polymerization reaction causing the performance of the synthesized polycarboxylate water reducer to decrease. However, the slow dripping of AB materials and constant temperature control increase the complexity of the synthesis process of polycarboxylate water reducer, and the synthesis cost is relatively high. In particular, the demand for collapse-preserving polycarboxylate water reducer is increasing. In order to prepare collapse-preserving polycarboxylate water reducer, it is often necessary to add collapse-preserving functional monomers, which puts higher requirements on the synthesis process. Summary of the invention

[0003] In view of the problems existing in the above-mentioned background technology, the present invention provides a method for preparing a collapse-preserving polycarboxylic acid water-reducing agent, which uses VPEG as a macromonomer and methyl acrylate as a collapse-preserving functional monomer, and effectively realizes the synthesis of a polycarboxylic acid water-reducing agent under room temperature conditions without the need for dripping time control and with a simple synthesis process.

[0004] The present invention provides a method for preparing a collapse-retaining polycarboxylate water-reducing agent, comprising the following steps:

[0005] (1) Synthesis of chitosan-acrylic acid composite microspheres: acrylic acid, hydroquinone and chitosan are dissolved in water, and then a liquid oil phase is added and ultrasonically dispersed to form an emulsion; the temperature is then raised to 40-60°C, and stirring is continued for more than 30 minutes under this condition to allow chitosan to gradually form a gel network and form a cross-linked entangled structure with acrylic acid and hydroquinone; hot air flow spray is then used to evaporate water, thereby obtaining chitosan-acrylic acid composite microspheres with chitosan as the gel network structure and acrylic acid and hydroquinone embedded in the gel network;

[0006] (2) Synthesis of chitosan-methyl acrylate microspheres: chitosan, methyl acrylate, p-quinone and VC are dissolved in an aqueous solution, and then a liquid oil phase is added, and ultrasonic dispersion is performed to uniformly form an emulsion; the temperature is then rapidly raised to 40-60°C, and stirring is continued for 30 min or more under this condition to allow the chitosan to gradually form a gel network and form a cross-linked entangled structure with methyl acrylate and p-quinone; hot air spray is then used to evaporate water, thereby obtaining chitosan-methyl acrylate microspheres with chitosan as the gel network structure and methyl acrylate, p-quinone and VC embedded in the gel network;

[0007] (3) pouring the chitosan-acrylic acid composite microspheres obtained in step (1) and the chitosan-methyl acrylate microspheres obtained in step (2) into a mixed solution of VPEG, hydrogen peroxide and sodium hypophosphite, and starting a stirring reaction for 2 hours;

[0008] (4) After the reaction in step (3) is completed, cold water at a temperature of 0 to 10° C. is added to control the solid content of the mixture to be 40% to 50%. After the solution temperature is 10° C. or below, the mixture is filtered and compressed to filter out the gel material to obtain the collapse-retaining polycarboxylic acid water-reducing agent of the present invention. The purpose of adding cold water is to lower the solution temperature on the one hand and to control the solid content of the mixed solution on the other hand.

[0009] Furthermore, the mass fractions of each raw material component in step (1) of the present invention are as follows:

[0010]

[0011] The mass fractions of each raw material component in step (2) are as follows:

[0012]

[0013] The mass fractions of each raw material component in step (3) are as follows:

[0014] VPEG 70-80 parts,

[0015] 1 to 1.5 parts of sodium hypophosphite,

[0016] 0.6-0.9 parts of hydrogen peroxide;

[0017] The mass fractions of the above raw material components are consistent;

[0018] The mass concentration of the hydrogen peroxide is 27.5%.

[0019] Furthermore, the liquid oil phase of the present invention is selected from any one of liquid vegetable oil and silicone oil.

[0020] Furthermore, in the step (1) and the step (2) of the present invention, 100 parts of liquid oil phase are added and ultrasonic dispersion is performed, so that the diameter of the water phase particles in the emulsion, that is, the chitosan-acrylic acid composite microspheres in the step (1) and the chitosan-methyl acrylate microspheres in the step (2), are effectively controlled between 0.1 mm and 1 mm. If the diameter is less than 0.1 mm, excessive acrylic acid will be released in the early stage, resulting in a large amount of self-polymerization to form polyacrylic acid, which will affect the normal reaction of polycarboxylic acid. If the diameter is greater than 1 mm, the release of acrylic acid will be slowed down in the later stage, which will affect the normal reaction of polycarboxylic acid.

[0021] The hydroquinone in step (1) has the effect of a polymerization inhibitor, but it only occurs under aerobic conditions, and is formed into microspheres together with acrylic acid and chitosan.

[0022] In step (2) of the present invention, p-quinone has a slow polymerization effect on methyl acrylate. When used in combination with methyl acrylate, effective polymerization regulation can be achieved for methyl acrylate. However, p-quinone used alone has limited effect. It is formed into microspheres with chitosan. Chitosan gradually dissolves and precipitates methyl acrylate, p-quinone and VC during use, which can achieve the purpose of slowly releasing methyl acrylate, making the polymerization of methyl acrylate and VPEG more stable. In addition, chitosan forms a gel state when the temperature rises to above 35°C. Compared with the dissolved state, the gel state has a significant inhibitory effect on the release of methyl acrylate and p-quinone, avoiding their release under high temperature conditions.

[0023] If the chitosan content in step (2) is too high, methyl acrylate cannot be released, the reaction is too slow, and the collapse retention of the polycarboxylic acid is affected; if the chitosan content is too low, methyl acrylate is released too quickly, the retarding effect is not obvious, and the product undergoes explosion polymerization, resulting in a decrease in dispersibility. Secondly, the content of quinone should be well controlled. Excessive chitosan content causes methyl acrylate to participate in the polymerization reaction too slowly, resulting in too few ester groups in the synthesized polycarboxylic acid, and its collapse retention performance is poor; too little chitosan content causes insufficient control over the self-polymerization of methyl acrylate, causing methyl acrylate to self-polymerize, affecting its polymerization with the polycarboxylic acid, resulting in a decrease in collapse retention. At the same time, the VC reduction system is slowly released under the constraint of chitosan microspheres, ensuring the stability of the redox system in the solution and achieving a replacement for the dripping method.

[0024] The reason why the temperature is lowered to 0-10°C in step (4) of the present invention is that the polyacrylic acid swelling sol coating layer formed on the surface of the chitosan-acrylic acid composite microspheres during the polycarboxylic acid synthesis reaction will shrink in volume under low temperature conditions, which can promote the rapid precipitation of the microspheres in the solution and achieve rapid separation from the solution.

[0025] When the microspheres obtained in step (1) of the present invention participate in the polycarboxylic acid reaction, chitosan dissolves and releases a large amount of acrylic acid. At this time, acrylic acid undergoes a polymerization reaction with VPEG under the redox system of hydrogen peroxide and VC. At the same time, acrylic acid is gradually released from chitosan, and the surrounding concentration increases. When hydroquinone encounters oxygen in the solution, an inhibitory effect is generated to prevent acrylic acid from self-polymerization, and at the same time, the reaction rate of acrylic acid and VPEG is effectively controlled. Further, as acrylic acid is gradually released from chitosan, a high concentration of acrylic acid is formed around chitosan. Although there is an inhibitory effect of hydroquinone, self-polymerization still occurs under the redox system. At this time, the generated polyacrylic acid is wrapped around chitosan to form a swollen gel, which is beneficial to controlling the further dissolution of acrylic acid and the synthesis rate of the polycarboxylic acid water reducer. At the same time, when the reaction temperature of acrylic acid and VPEG in the solution rises to the LCST of the chitosan microspheres (generally between 35 and 40° C.), the chitosan microspheres are gelled, further hindering the dissolution of acrylic acid, preventing the polycarboxylic acid water reducer from reacting under high temperature conditions, and avoiding adverse reactions under high temperature conditions. VPEG has high activity and belongs to a macromonomer synthesized at room temperature. When the synthesis temperature is too high, its activity increases, resulting in an intensified reaction, and implosion is likely to occur, affecting the dispersibility of the polycarboxylic acid water-reducing agent. In the present invention, to achieve the above effect, first, the dosage of chitosan must be controlled (if the dosage is too high, the gel system formed is too large, which hinders the stable release of acrylic acid; if the dosage is too low, the acrylic acid dissolves faster when it is in a dissolved state, and after the gel is formed, the acrylic acid dissolution cannot be well controlled), and secondly, a microsphere structure must be formed, and furthermore, the dosage of hydroquinone must be controlled (if the dosage is too high, the inhibition effect is too strong, affecting the normal synthesis of polycarboxylic acid, and if the dosage is too low, the inhibition effect is not obvious, resulting in aggravated self-polymerization of acrylic acid, implosion occurs in the synthesis of polycarboxylic acid, and affecting product performance).

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) Achieved good synthesis of polycarboxylate water reducer;

[0028] (2) The adverse effects of acrylic acid self-polymerization and acrylic acid explosion polymerization during the synthesis of acrylic acid and VPEG were effectively controlled, and the reaction rate was effectively controlled; at the same time, due to the excessively high concentration around the chitosan microspheres during the release of acrylic acid, when hydroquinone has not yet exerted its inhibitory effect, an acrylic acid self-polymerization network layer will be formed around the microspheres. This can further utilize the thermosensitive effect of polyacrylic acid and chitosan under different temperature conditions. Chitosan and p-quinone effectively control the release of acrylic acid under different temperature conditions during the synthesis of polycarboxylic acid water reducer. In the entire preparation process, an inhibitor is used for acrylic acid, mainly to prevent acrylic acid from self-polymerizing in large quantities under high concentration conditions, and a retarder is used for methyl acrylate, mainly to control its self-polymerization and the polymerization rate with VPEG;

[0029] (3) In the present invention, acrylic acid microspheres and methyl acrylate microspheres are prepared separately, so that different retarding components can effectively target different monomers, achieve targeted polymerization control, achieve a good polymerization process of polycarboxylic acid, control the polymerization temperature, and achieve good performance of the product. DETAILED DESCRIPTION

[0030] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form.

[0031] Example 1

[0032] The raw materials for synthesizing the polycarboxylate water-reducing agent of the present invention include:

[0033]

[0034] Its preparation method is:

[0035] (1) Preparation of chitosan-acrylic acid composite microspheres: acrylic acid, hydroquinone and chitosan are dissolved in an aqueous solution (4 parts by weight of chitosan and 20 parts by weight of water), then added to 100 parts of peanut oil phase, and ultrasonically dispersed to form an emulsion; then the temperature is rapidly raised to 60°C, and stirring is continued for 30 minutes under this condition, and then hot air spray is used to evaporate water, thereby forming porous chitosan-acrylic acid composite microspheres;

[0036] (2) Preparation of chitosan-methyl acrylate microspheres: chitosan, methyl acrylate, p-quinone and VC were dissolved in an aqueous solution (8 parts by weight of chitosan and 50 parts by weight of water), and then 150 parts of peanut oil phase were added and ultrasonically dispersed to form an emulsion; then the temperature was quickly raised to 40°C, and under this condition, the mixture was stirred evenly and ultrasonically dispersed for 30 minutes, and then hot air spray was used to evaporate the water, thereby forming porous chitosan-methyl acrylate microspheres;

[0037] (3) Pour chitosan-acrylic acid composite microspheres and chitosan-methyl acrylate microspheres into a mixed solution of VPEG, hydrogen peroxide and sodium hypophosphite, and start stirring the reaction for 2 h;

[0038] (4) After the reaction is completed, cold water at a temperature of 10° C. is added to control the solid content of the mixture to 50%, and the solution temperature is filtered at 10° C. to filter out the gel material to obtain the collapse-retaining polycarboxylate water-reducing agent.

[0039] Example 2

[0040] The raw materials for synthesizing the polycarboxylate water-reducing agent of the present invention include:

[0041]

[0042] Its preparation method is:

[0043] (1) Preparation of chitosan-acrylic acid composite microspheres: acrylic acid, hydroquinone and chitosan are dissolved in a solution (6 parts by weight of chitosan and 30 parts by weight of water), and then sufficient methyl silicone oil is added and ultrasonically dispersed to form an emulsion; then the temperature is rapidly raised to 40°C, and stirring is continued for 30 minutes under this condition, and then hot air spray is used to evaporate water, thereby forming porous chitosan-acrylic acid composite microspheres;

[0044] (2) Preparation of chitosan-methyl acrylate microspheres: chitosan, methyl acrylate, p-quinone and VC were dissolved in a solution (chitosan was 10 parts by weight and water was 40 parts by weight), and then 150 parts of methyl silicone oil were added and ultrasonically dispersed to form an emulsion; then the temperature was quickly raised to 60°C, and under this condition, the mixture was stirred evenly and ultrasonically dispersed for 30 minutes, and then hot air was sprayed to evaporate the water, thereby forming porous chitosan-methyl acrylate microspheres;

[0045] (3) Pour chitosan-acrylic acid composite microspheres and chitosan-methyl acrylate microspheres into a mixed solution of VPEG, hydrogen peroxide and sodium hypophosphite, and start stirring the reaction for 2 h;

[0046] (4) After the reaction is completed, cold water at a temperature of 4° C. is added to control the solid content of the mixture to 40%, and the solution temperature is adjusted to be filtered at 4° C. to filter out the gel material to obtain the collapse-retaining polycarboxylate water reducer.

[0047] Example 3

[0048] The raw materials for synthesizing the polycarboxylate water-reducing agent of the present invention include:

[0049]

[0050]

[0051] Its preparation method is:

[0052] (1) Preparation of chitosan-acrylic acid composite microspheres: acrylic acid, hydroquinone and chitosan are dissolved in a solution (5 parts by weight of chitosan and 25 parts by weight of water), and then 100 parts of polydimethylsiloxane are added and ultrasonically dispersed to form an emulsion; then the temperature is rapidly raised to 50° C., and stirring is continued for 30 minutes under this condition, and then hot air spray is used to evaporate water, thereby forming porous chitosan-acrylic acid composite microspheres;

[0053] (2) Preparation of chitosan-methyl acrylate microspheres: chitosan, methyl acrylate, p-quinone and VC were dissolved in a solution (chitosan was 10 parts by weight and water was 40 parts by weight), and then 150 parts of polydimethylsiloxane oil phase was added, and ultrasonic dispersion was performed to form an emulsion; then the temperature was quickly raised to 50°C, and under this condition, the mixture was stirred evenly and ultrasonic dispersion was continued for 30 minutes, and then hot air spray was used to evaporate the water, thereby forming porous chitosan-methyl acrylate microspheres;

[0054] (3) Pour chitosan-acrylic acid composite microspheres and chitosan-methyl acrylate microspheres into a mixed solution of VPEG, hydrogen peroxide and sodium hypophosphite, and start stirring the reaction for 2 h;

[0055] (4) After the reaction is completed, cold water at a temperature of 6° C. is added to control the solid content of the mixture to 45%, and the solution is filtered at a temperature of 6° C. to filter out the gel material to obtain a collapse-retaining polycarboxylic acid water reducer.

[0056] Benchmark Example:

[0057] The difference from Example 3 is that chitosan microspheres are not prepared, hydroquinone and p-quinone are not added, steps (1) and (2) are omitted, and in step (3), acrylic acid is slowly added dropwise for 40 min, methyl acrylate and VC are slowly added dropwise for 50 min, the dropping and synthesis time is controlled within 2 h, and the synthesis temperature is controlled within a water bath condition within a range of 15° C. to 35° C.; the synthesis conditions are the optimal synthesis conditions for preparing the collapse-retaining polycarboxylic acid water-reducing agent in the present invention.

[0058] Comparative Example 1

[0059] The difference from Example 3 is that chitosan microspheres are not prepared, and steps (1) and (2) are omitted. In step (3), hydroquinone and acrylic acid are slowly added dropwise for 40 min, and methyl acrylate, VC and p-quinone are slowly added dropwise for 50 min. The addition and synthesis time are controlled within 2 h.

[0060] Comparative Example 2

[0061] The difference from Example 3 is that no microspheres are prepared, and there are no steps (1) and (2). Only in step (3), acrylic acid, hydroquinone, methyl acrylate, VC, and p-quinone are mixed and then directly added.

[0062] Comparative Example 3

[0063] The difference from Example 3 is that chitosan microspheres are not prepared, steps (1) and (2) are omitted, and only in step (3) are acrylic acid, methyl acrylate and VC directly added.

[0064] Comparative Example 4

[0065] The difference from Example 3 is that the chitosan-acrylic acid microspheres contain 1 part of chitosan.

[0066] Comparative Example 5

[0067] The difference from Example 3 is that the chitosan-acrylic acid microspheres contain 10 parts of chitosan.

[0068] Comparative Example 6

[0069] The difference from Example 3 is that during the preparation of chitosan-acrylic acid microspheres, after the emulsion is formed, the temperature is not raised to 50° C., but the preparation is directly performed at room temperature.

[0070] Comparative Example 7

[0071] The difference from Example 3 is that during the preparation of chitosan-acrylic acid microspheres, the water content is 10 parts.

[0072] Comparative Example 8

[0073] The difference from Example 3 is that during the preparation of chitosan-acrylic acid microspheres, the water content is 40 parts.

[0074] Comparative Example 9

[0075] The difference from Example 3 is that during the preparation of chitosan-acrylic acid microspheres, 0.001 parts of hydroquinone are used.

[0076] Comparative Example 10

[0077] The difference from Example 3 is that during the preparation of chitosan-acrylic acid microspheres, 0.01 part of hydroquinone is used.

[0078] Comparative Example 11

[0079] The difference from Example 3 is that during the preparation of chitosan-methyl acrylate microspheres, 1 part of chitosan is used.

[0080] Comparative Example 12

[0081] The difference from Example 3 is that during the preparation of chitosan-methyl acrylate microspheres, 15 parts of chitosan are used.

[0082] Comparative Example 13

[0083] The difference from Example 3 is that during the preparation process of chitosan-methyl acrylate microspheres, after the emulsion is formed, the temperature is not raised to 50° C., but the preparation is directly performed at room temperature.

[0084] Comparative Example 14

[0085] The difference from Example 3 is that during the preparation of chitosan-acrylic acid microspheres, the water content is 30 parts.

[0086] Comparative Example 15

[0087] The difference from Example 3 is that during the preparation of chitosan-methyl acrylate microspheres, the water content is 60 parts.

[0088] Comparative Example 16

[0089] The difference from Example 3 is that in the chitosan-methyl acrylate microspheres, 0 part of p-quinone;

[0090] Comparative Example 17

[0091] The difference from Example 3 is that in the chitosan-methyl acrylate microspheres, 0.05 parts of p-quinone;

[0092] Comparative Example 18

[0093] The difference from Example 3 is that in step (4), the solution temperature is not controlled below 10°C, and water is directly added at room temperature (20°C).

[0094] The test indicators and test methods of the above embodiments and comparative examples were tested according to the provisions of "Polycarboxylic Acid High Performance Water Reducer" JG / T223-2017. The main test indicators were water reduction rate, slump loss over time and 28d compressive strength ratio. The results are shown in Table 1.

[0095] Table 1 Water reduction performance index test results

[0096]

[0097]

[0098] As can be seen from Table 1, in Example 1, the water reduction rate is 32.5%, the slump losses over time at 1h, 2h, and 3h are 0mm, 10mm, and 20mm, respectively, and the 28d compressive strength ratio is 164.2%.

[0099] In Example 2, the water reduction rate is 32.8%, the slump losses over time at 1h, 2h, and 3h are 0mm, 5mm, and 20mm, respectively, and the 28d compressive strength ratio is 159.5%.

[0100] In Example 3, the water reduction rate is 33.5%, the slump losses over time at 1h, 2h, and 3h are 0mm, 5mm, and 15mm, respectively, and the 28d compressive strength ratio is 168.6%.

[0101] In the benchmark example, the water reduction rate is 29.8%, the slump losses after 1h, 2h and 3h are 5mm, 25mm and 40mm respectively, and the 28d compressive strength ratio is 142.7%.

[0102] Comparing Examples 1 to 3 with the reference example, it can be seen that the polycarboxylate water-reducing agent prepared in the reference example has good dispersibility and good slump retention, and has a significant effect on improving concrete strength, but it is necessary to control the synthesis temperature and the drop-adding time during synthesis, and the synthesis conditions require precise control. In Examples 1 to 3, the drop-adding time and the synthesis temperature during the polycarboxylate synthesis process are not controlled, and the water reduction rate, slump retention and the effect of improving concrete strength are further improved, and the synthesis effect is better.

[0103] In comparative example 1, the water reduction rate is 23.1%, and the 1h, 2h, and 3h slump losses of concrete are 45mm, 80mm, and 120mm respectively, and the 28d compressive strength ratio is 108.4%. Compared with Example 3 and the benchmark example, the water reduction rate decreases, the slump retention type decreases, and the compressive strength improvement effect decreases. This shows that when microspheres are not prepared, first, due to the influence of the presence of hydroquinone inhibitor, the polymerization of acrylic acid and VPEG is affected, the molecular weight is small, the dispersibility decreases, and the water reduction rate decreases. Secondly, due to the influence of the presence of the p-gaoquinone retarder, the polymerization of methyl acrylate and VPEG is hindered, the ester group is reduced, and the slump retention type decreases. This shows that if microspheres are not prepared, only the addition of hydroquinone and p-gaoquinone will cause slow reaction, poor polymerization effect, poor dispersibility, poor slump retention, and poor improvement of concrete mechanical properties.

[0104] In comparative example 2, the water reduction rate is 24.8%, and the slump loss of concrete 1h, 2h, and 3h over time is 55mm, 85mm, and 130mm respectively, and the 28d compressive strength ratio is 108.6%. Compared with Example 3 and the benchmark example, the water reduction rate decreases, the slump protection type decreases, and the compressive strength improvement effect decreases. This is because due to the influence of the presence of hydroquinone inhibitor, the polymerization of acrylic acid and VPEG is affected, the molecular weight is small, the dispersibility decreases, and the water reduction rate decreases. At the same time, all components are added together, and the concentration in the solution is too high, resulting in the same component reaction self-polymerization and different component reaction explosion polymerization. The redox system concentration is high, resulting in many impurities in the reaction product, and the performance of the water reducer generated by polymerization is poor. Secondly, due to the influence of the presence of the Gaoquinone retarder, the polymerization of methyl acrylate and VPEG is hindered, the ester group is reduced, and the slump protection type decreases. At the same time, due to the high concentration, self-polymerization is prone to occur, resulting in many product impurities, and the slump protection group content of the polycarboxylic acid water reducer itself is further reduced, so the slump protection type is further reduced. The decline in the performance of the mixture further has an adverse effect on the mechanical properties, and its 28d compressive strength ratio decreases. However, compared with Comparative Example 1, there is no significant difference in the performance indicators. This shows that when the polymerization inhibitor and the retarder participate in the polymerization reaction, the difference in the effect of the drop time can be significantly reduced, but the performance of the synthesized water reducer is significantly reduced after addition.

[0105] In comparative example 3, the water reduction rate is 16.7%, the slump loss of concrete 1h, 2h, 3h is 65mm, 100mm, 160mm respectively, and the 28d compressive strength ratio is 96.5%. Compared with the embodiment and the benchmark example, this is because all the components are added together, the concentration in the solution is too high, resulting in the same component reaction self-polymerization, different component reaction explosion polymerization, high concentration of redox system, resulting in many impurities in the reaction product, and the performance of the polymerized water reducer is poor. Due to the high concentration of methyl acrylate, self-polymerization occurs, and the slump-retaining group content of the polycarboxylate water reducer itself is further reduced, so the slump-retaining type is further reduced, which also affects the improvement of the compressive strength of concrete.

[0106] In Comparative Example 4, the water reduction rate is 24.4%, the slump losses of the concrete after 1h, 2h and 3h are 15mm, 35mm and 75mm respectively, and the 28d compressive strength ratio is 120.4%.

[0107] In Comparative Example 5, the water reduction rate is 22.0%, the slump loss of concrete after 1h, 2h and 3h is 20mm, 45mm and 70mm respectively, and the 28d compressive strength ratio is 115.4%.

[0108] Comparative Example 3, Comparative Example 4 and Comparative Example 5 analyze that when the chitosan dosage is too low, the chitosan microsphere structure formed is relatively weak, and it is more soluble in the solution, and acrylic acid and hydroquinone are more easily released, and the rate of release is faster. The dosage setting of hydroquinone can ensure that a good polymerization inhibition effect is formed on acrylic acid in the microsphere, but when released into the entire reaction system, its concentration decreases rapidly, and the polymerization inhibition effect on acrylic acid is reduced. Especially when the release rate is too fast, its concentration is high, and the polymerization inhibition effect of hydroquinone on acrylic acid is limited under anaerobic conditions. When acrylic acid is not fully dispersed in the solution, a large amount of self-polymerization occurs by itself, and a stable polymerization reaction cannot occur with VPEG, resulting in a lack of carboxyl groups in the synthesized polycarboxylate water-reducing agent (acrylic acid contains a large number of carboxyl groups), lack of adsorption to cement, resulting in its dispersibility weakening, and a decrease in water reduction rate. Moreover, under high temperature conditions (when chitosan LSCT is reached), the restriction on the release of acrylic acid is weakened when chitosan is in the thermosensitive phase transition microgel state, and acrylic acid cannot be prevented from being further released, so the synthesis temperature during the reaction cannot be effectively controlled, resulting in an increase in the synthesis temperature during the reaction, causing the reaction to be unstable, and also causing the dispersibility of the synthesized polycarboxylic acid to decrease. When chitosan is increased to an appropriate dosage, the microspheres formed can more effectively control (slow down) the release rate of acrylic acid and hydroquinone. Although there is a certain amount of excess acrylic acid that forms polyacrylic acid on the surface of chitosan and then adheres to the surface of chitosan to form a gel state, due to the stable release rate, when hydroquinone is gradually released into the solution, it encounters oxygen to produce an inhibitory effect, which can control the polymerization of acrylic acid itself, thereby ensuring the stable release of acrylic acid into the solution. When released into the solution, the concentration of hydroquinone decreases, and the inhibitory effect on the synthesis of polycarboxylic acid decreases, ensuring the normal synthesis of polycarboxylic acid water reducer. When the chitosan dosage is further increased, the gel content formed by chitosan is too high. A large amount of gel is formed under high temperature conditions, which completely hinders the release of acrylic acid, causing the reaction of acrylic acid and VPEG to stop completely, resulting in uneven product structure and decreased performance. Therefore, the water reduction rate decreases. Acrylic acid participates in the synthesis reaction with VPEG in a disordered manner, further causing disorder in the polymerization of methyl acrylate and VPEG, reducing the ester group in the product, and reducing the collapse retention type of incorporation.

[0109] In comparative example 6, the water reduction rate is 22.6%; the slump loss of concrete in 1h, 2h and 3h is 20mm, 45mm and 75mm respectively, and the 28d compressive strength ratio is 118.3%. The purpose of heating is to make chitosan undergo gelation transformation, realize the attachment and wrapping of acrylic acid and hydroquinone, and adjust the morphology of microspheres in advance through heating measures to ensure stable release in the solution later. If the temperature is not raised, the microspheres formed are irregular, and the release rate of acrylic acid and hydroquinone is difficult to control well, which affects the polymerization effect.

[0110] In comparative example 7, the water reduction rate is 23.5%; the slump loss of concrete after 1h, 2h and 3h is 15mm, 40mm and 65mm respectively, and the compressive strength ratio is 129.4%. Compared with example 3, the water reduction rate, slump retention and strength improvement effect are all reduced. This shows that the water content is too low, so that the dispersion of chitosan, acrylic acid and hydroquinone is not uniform, the viscosity is too high, and the size of the formed microspheres is irregular, which affects the polymerization reaction.

[0111] In comparative example 8, the water reduction rate is 24.6%; the slump loss of concrete in 1h, 2h and 3h is 25mm, 40mm and 70mm respectively, and the compressive strength ratio is 122.6%. Compared with Example 3, its water reduction rate, slump retention and strength improvement effect are all reduced. This is because the water content is too high, resulting in a decrease in chitosan concentration, too many microspheres, and too fast release of acrylic acid, resulting in acrylic acid self-polymerization, and affecting the performance of the synthesized water reducer.

[0112] In Comparative Example 9, the water reduction rate is 20.5%; the slump loss of concrete after 1h, 2h and 3h is 10mm, 30mm and 60mm respectively, and the 28d compressive strength ratio is 109.4%.

[0113] In Comparative Example 10, the water reduction rate is 18.7%; the slump losses of the concrete after 1h, 2h and 3h are 25mm, 55mm and 85mm respectively, and the 28d compressive strength ratio is 99.8%.

[0114] Compared with Example 3, the performance of the water reducer synthesized by Comparative Examples 9 and 10 is reduced. Analysis of the reasons: The difference between the comparative examples and Example 3 lies in the content of hydroquinone. Hydroquinone mainly plays an inhibitory effect on acrylic acid. It is prepared into microspheres together with acrylic acid to prevent itself from self-polymerization in large quantities. At the same time, hydroquinone will only produce an inhibitory effect under aerobic conditions. Therefore, when it is released from the microspheres into the solution, it effectively avoids the large-scale self-polymerization of acrylic acid under high concentration conditions before the polymerization of acrylic acid and VPEG. At the same time, due to the large volume of the synthetic solution, the hydroquinone is dispersed and diluted, reducing its inhibitory effect, so it has little effect on the synthesis of acrylic acid and VPEG. When its dosage is too low, the self-polymerization of acrylic acid cannot be effectively controlled. When its dosage is too high, it affects the synthesis of polycarboxylic acid by acrylic acid and VPEG, resulting in a decrease in the water reduction rate and a decrease in the collapse retention performance.

[0115] In Comparative Example 11, the water reduction rate is 26.3%; the slump loss of concrete at 1h, 2h and 3h is 35mm, 75mm and 105mm respectively, and the 28d compressive strength ratio is 138.2%.

[0116] In Comparative Example 12, the water reduction rate is 25.9%; the slump losses of the concrete after 1h, 2h and 3h are 40mm, 85mm and 110mm respectively, and the 28d compressive strength ratio is 133.6%.

[0117] Comparative Example 3, Comparative Example 11 and Comparative Example 12 are analyzed, and the performance of the water reducer prepared in the comparative example is all decreased. This is because when the chitosan dosage is too low, the chitosan microsphere structure formed is relatively weak, and it is more soluble in the solution, and methyl acrylate, p-quinone and VC are more easily released, and the rate of release is faster. The dosage setting of p-quinone can ensure that a good retarding effect is formed on methyl acrylate in the microsphere, but when released into the entire reaction system, its concentration decreases rapidly, and the retarding effect on methyl acrylate is reduced. Especially when the release rate is too fast, its concentration is high, methyl acrylate and VPEG undergo implosion and self-polymerization, resulting in a large difference in the molecular weight of the synthesized polycarboxylic acid water reducer, product hybridization, and a decrease in water reduction rate and collapse retention type. Moreover, under high temperature conditions (when chitosan LSCT is reached), the chitosan thermosensitive phase change microgel state weakens the restraint on the release of methyl acrylate, and it is unable to prevent the further release of methyl acrylate, thus failing to effectively control the synthesis temperature during the reaction, causing the synthesis temperature to rise during the reaction, resulting in reaction instability, and also causing the synthesized polycarboxylic acid to have a decreased collapse retention. When the chitosan dosage is increased to an appropriate level, the formed microspheres can more effectively control (slow down) the release rate of methyl acrylate, p-quinone, and VC, thereby ensuring the stable release of methyl acrylate into the solution, effectively controlling the release amount of VC and methyl acrylate in the solution, and ensuring the normal synthesis of the polycarboxylic acid water reducer. When the chitosan dosage is further increased, the gel content formed by chitosan is too high, and a large amount of gel formed under high temperature conditions completely hinders the release of methyl acrylate, causing the reaction of methyl acrylate with VPEG to stop completely, resulting in an uneven product structure, a reduction in ester groups, and a decrease in collapse retention.

[0118] The water reduction rate in Comparative Example 13 is 26.1%; the slump loss of concrete at 1h, 2h and 3h is 35mm, 65mm and 90mm respectively, and the 28d compressive strength ratio is 130.5%. Compared with Example 3, the performance of the synthesized water reducer has declined. Analysis of the reasons: The purpose of heating is to make chitosan undergo gelation transformation, to achieve the attachment and wrapping of methyl acrylate, VC and p-gaoquinone, and to adjust the morphology of the microspheres in advance through heating measures to ensure stable release in the solution later. If the temperature is not increased, the formed microspheres are irregular, and the release rate of methyl acrylate, VC and p-gaoquinone is difficult to control well, which affects the polymerization effect.

[0119] In comparative example 14, the water reduction rate is 25.8%; the slump loss of concrete at 1h, 2h and 3h is 25mm, 60mm and 85mm respectively, and the 28d compressive strength ratio is 132.7%. Compared with Example 3, the performance of the synthesized water reducer is reduced. This is because the water content is too low, so that the chitosan, methyl acrylate and p-quinone are not dispersed uniformly, the viscosity is too high, and the size of the formed microspheres is irregular, which affects the polymerization reaction.

[0120] In comparative example 15, the water reduction rate is 26.4%; the slump loss of concrete at 1h, 2h and 3h is 25mm, 55mm and 80mm respectively, and the 28d compressive strength ratio is 138.0%. Compared with Example 3, the performance of the synthesized water reducer is reduced. This is because the water content is too high, resulting in too many pores in the synthesized microspheres, and the methyl acrylate and VC are released too quickly, which makes it easy to explode during the synthesis process and affects the performance of the synthesized water reducer.

[0121] In Comparative Example 16, the water reduction rate is 25.5%; the slump losses of the concrete after 1h, 2h and 3h are 45mm, 85mm and 105mm respectively, and the 28d compressive strength ratio is 134.7%.

[0122] In Comparative Example 17, the water reduction rate is 26.4%; the slump loss of concrete at 1h, 2h and 3h is 40mm, 75mm and 95mm respectively, and the 28d compressive strength ratio is 129.5%.

[0123] Comparison of Comparative Examples 16 and 17 with Example 3 shows that the performance of the water reducers prepared in the comparative examples has decreased. The reason for the analysis is that the difference in the synthesis process lies in the content of paraquinone. Paraquinone mainly plays a retarding effect on methyl acrylate. It is prepared into microspheres together with methyl acrylate to prevent its own large-scale self-polymerization and delay the self-polymerization reaction. Before methyl acrylate and VPEG are polymerized, a large amount of self-polymerization of methyl acrylate under high concentration conditions is effectively avoided, and the explosion phenomenon is effectively prevented during the polymerization of methyl acrylate and VPEG. When its dosage is too low, it is impossible to effectively control the self-polymerization of methyl acrylate and its explosion with VPEG. When its dosage is too high, it affects the synthesis of polycarboxylic acid by methyl acrylate and VPEG, resulting in a decrease in collapse retention performance.

[0124] The water reduction rate in Comparative Example 18 is 27.8%; the slump loss of concrete at 1h, 2h, and 3h is 15mm, 30mm, and 50mm, respectively, and the 28d compressive strength ratio is 140.2%. Compared with Example 3, the performance of the synthesized water reducer has declined. The reason for the analysis is that the filtration at 0-10°C is that as the reaction proceeds, the acrylic acid in the solution is gradually consumed, the solubility of chitosan decreases, and it gradually precipitates, but the polyacrylic acid coating layer formed on its surface is still in a dissolved state. When the temperature is lowered to below 10°C, the polyacrylic acid shrinks sensitively to form a gel, which can be removed by filtration. When water is added and filtered at room temperature, the polyacrylic acid cannot be removed, resulting in more impurities in the product, affecting the performance.

[0125] The above-mentioned water reducer is tested for the water reduction rate of concrete in accordance with the provisions of JG / T 223-2017 "Polycarboxylic acid-based high performance water reducer". On the basis of the determined water reduction rate, the slump of concrete out of the machine is controlled to be 210mm in accordance with the provisions of JG / T 223-2017 "Polycarboxylic acid-based high performance water reducer", and the 1h slump loss over time, 2h slump loss over time and 3h slump loss over time of concrete are tested.

Claims

1. A method for preparing a collapse-retaining polycarboxylate water-reducing agent, characterized in that: The steps include: (1) Synthesis of chitosan-acrylic acid composite microspheres: acrylic acid, hydroquinone and chitosan are dissolved in water, and then a liquid oil phase is added and uniformly dispersed by ultrasonication to form an emulsion; then the temperature is raised to 40-60°C, and stirring is continued for more than 30 minutes under this condition, and then hot air flow spray is used to evaporate water to obtain chitosan-acrylic acid composite microspheres with chitosan as a gel network structure and acrylic acid and hydroquinone embedded in the gel network; (2) Synthesis of chitosan-methyl acrylate microspheres: chitosan, methyl acrylate, p-quinone and VC are dissolved in an aqueous solution, and then a liquid oil phase is added, and ultrasonic dispersion is performed to form an emulsion; then the temperature is rapidly raised to 40-60°C, and stirring is continued for 30 min or more under this condition, and then hot air spray is used to evaporate water to obtain chitosan-methyl acrylate microspheres with chitosan as a gel network structure and methyl acrylate, p-quinone and VC embedded in the gel network; (3) pouring the chitosan-acrylic acid composite microspheres obtained in step (1) and the chitosan-methyl acrylate microspheres obtained in step (2) into a mixed solution of VPEG, hydrogen peroxide and sodium hypophosphite, and starting a stirring reaction for 2 hours; (4) After the reaction in step (3) is completed, cold water at a temperature of 0 to 10° C. is added to control the solid content of the mixture to be 40% to 50%, and the solution temperature is 10° C. or below, and then filtered and compressed to filter out the gel material to obtain the collapse-retaining polycarboxylic acid water-reducing agent.

2. The method for preparing a collapse-retaining polycarboxylate water-reducing agent according to claim 1, characterized in that: The mass fractions of each raw material component in step (1) are as follows: The mass fractions of each raw material component in step (2) are as follows: The mass fractions of each raw material component in step (3) are as follows: VPEG 70-80 parts, 1 to 1.5 parts of sodium hypophosphite, 0.6-0.9 parts of hydrogen peroxide; The mass fractions of the above raw material components are consistent; The mass concentration of the hydrogen peroxide is 27.5%.

3. The method for preparing a collapse-retaining polycarboxylate water-reducing agent according to claim 1, characterized in that: The liquid oil phase is selected from any one of liquid vegetable oil and silicone oil.

4. The method for preparing a collapse-retaining polycarboxylate water-reducing agent according to claim 1, characterized in that: The diameters of the chitosan-acrylic acid composite microspheres in step (1) and the chitosan-methyl acrylate microspheres in step (2) are effectively controlled between 0.1 mm and 1 mm.